Evaluation of Phytochemical and Antioxidant Activity of Gomphrena celosioides Mart. Grown in Tien Giang Province, Vietnam - Thuy, Nguyen Van; Tien, Nguyen Minh; Quy, Nguyen Ngoc; Lam, Tri Duc; Kieu Linh, Huynh Thi; Trieu, Ly Hai; Minh, Le Van; Quan, Pham Minh; Bui, Le Minh; Truc, Tran Thanh; et al. (Asian Journal of Chemistry, 2019)
Gomphrena celosioides Mart. is well known for its medicinal values worldwide. In this study, three extracts, viz. diethyl ether extract (DEE), ethanolic extract (EE) and aqueous extract (AE), were successively obtained from the leaves and stem of Gomphrena celosioides to determine the polyphenol and flavonoid content in this plant. A wide variety of pharmacologically active compounds such as alkaloid, flavonoid, terpenoid, saponin, tannin and polyphenol compounds were present in Gomphrena celosioides. The results of quantitative determination showed that total polyphenol content of DEE, EE and AE reached 35.35 ± 1.47, 250.17 ± 2.95 and 133.92 ± 3.17 mgGAE/g, respectively. Moreover, total flavonoid content of the DEE, EE and AE was 23.21 ± 1.87, 50.74 ± 2.32 and 27.25 ± 1.34 mgQE/g, respectively.In comparison with DEE and AE, the ethanolic extract exhibited the highest DPPH (IC50 = 13.29 ± 0.10 μg/mL) and ABTS (IC50 = 6.3 ± 0.11 μg/mL).